The wildman of Shaggy Creek [videorecording (DVD)] - Edwards, Jesse; Baird, Scott; York, Rob; Hensley, Hudson; Hethcoat, Allee-Sutton; Futcher, Josh; Bullington, Ayla; Grimly, R. H. (BMG-Global, 2025)
Scott's move to a new town becomes a heart-pounding adventure when he accepts a dare to camp in the ominous woods. Armed only with his fearless friend Hailey, he must confront the legend of a terrifying creature lurking in the shadows.